The companion to development studies - Desai, Vandana, 1965-; Potter, Robert B. (London ; New York : Routledge, 2014)
"With over 115 concise and authoritative chapters covering a wide range of disciplines the book is divided into ten sections covering the nature of development, the theories and strategies of development, rural development, urbanization, gender, globalization, health and education, the political economy of violence and insecurity, environment and development, governance and development.This new third edition of The Companion to Development Studies is an essential read for students of development studies at all levels - from undergraduate to graduate - and across several disciplines including geography, international relations, politics, economics, sociology and anthropology"--
"The Companion to Development Studies contains over 109 chapters written by leading international experts within the field to provide a concise and authoritative overview of the key theoretical and practical issues dominating contemporary development studies. Covering a wide range of disciplines the book is divided into ten sections, each prefaced by a section introduction written by the editors. The sections cover: the nature of development, theories and strategies of development, globalization and development, rural development, urbanization and development, environment and development, gender, health and education, the political economy of violence and insecurity, and governance and development. This third edition has been extensively updated and contains 45 new contributions from leading authorities, dealing with pressing contemporary issues such as race and development, ethics and development, BRICs and development, global financial crisis, the knowledge based economy and digital divide, food security, GM crops, comparative urbanism, cities and crime, energy, water hydropolitics, climate change, disability, fragile states, global war on terror, ethnic conflict, legal rights to development, ecosystems services for development, just to name a few. Existing chapters have been thoroughly revised to include cutting-edge developments, and to present updated further reading and websites"--
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Economic development; Development economics; Globalization; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography; Developing countries -- Social conditions